1950
DOI: 10.1084/jem.91.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Edema in Influenzal Pneumonia of the Mouse and the Relation of Fluid in the Lung to the Inception of Pneumococcal Pneumonia

Abstract: In a preceding study (2) concerning the mechanism by which influenza viral infection of the mouse induces susceptibility to secondary pneumococ~l pneumonia evidence was presented that this susceptibility is associated with the appearance of the lesion produced by the virus. The studies reported in the present paper indicate that pulmonary edema is a component of the influenza viral lesion in the mouse and that the presence of fluid in the lung is an important factor in the inception of pneumococcal pneumonia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

1951
1951
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…The finding that some areas of consolidation did not contain extracellular bacteria or focal areas of bacteria-containing macrophages suggests that edema and consolidation, as proposed by others (17,18), are not the cause of suppressed bactericidal mechanims but rather may be the effect of enhanced bacterial proliferation.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…The finding that some areas of consolidation did not contain extracellular bacteria or focal areas of bacteria-containing macrophages suggests that edema and consolidation, as proposed by others (17,18), are not the cause of suppressed bactericidal mechanims but rather may be the effect of enhanced bacterial proliferation.…”
Section: Methodsmentioning
confidence: 64%
“…Male Swiss albino mice (CD 1 strain, [18][19][20] g) were used in these experiments. The animals were housed in filter-topped cages and fed food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies using bacteria presented as a bolus to the distal lung uniformly reported the presence of PMN in the alveoli within a few hours of the introduction of the bacteria (26)(27)(28)(29). Some investigators felt that the granulocytes were primarily responsible for the killing of the bacteria (30,31), whereas others attributed this function to the alveolar macrophage (32). More recent research (33)(34)(35) has focused on bacteria presented to the lungs in the form of a diffuse aerosol rather than a bolus, allowing large numbers of animals to receive a uniform dose of bacteria and permitting meaningful statistical evaluation of bacterial clearance kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this impairment is unclear. Ozone causes edema formation (23), and previous studies suggest that phagocytic mobility is hindered by intra-alveolar fluid (24). Because the histologic assessment of edema is a crude measureinent, it is possible that sufficient amounts of undetected edema fluid were present to hinder phagocvtosis.…”
Section: Methodsmentioning
confidence: 99%